Offensive Security Using Python. - Rejah Rehim; Manindar Mohan; Grant Ongers; PACKT (GB: Packt, 2024)
Unlock Python's hacking potential and discover the art of exploiting vulnerabilities in the world of offensive cybersecurity Key Features Get in-depth knowledge of Python's role in offensive security, from fundamentals through to advanced techniques Discover the realm of cybersecurity with Python and exploit vulnerabilities effectively Automate complex security tasks with Python, using third-party tools and custom solutions Purchase of the print or Kindle book includes a free PDF eBook Book Description Offensive Security Using Python is your go-to manual for mastering the quick-paced field of offensive security. This book is packed with valuable insights, real-world examples, and hands-on activities to help you leverage Python to navigate the complicated world of web security, exploit vulnerabilities, and automate challenging security tasks. From detecting vulnerabilities to exploiting them with cutting-edge Python techniques, you'll gain practical insights into web security, along with guidance on how to use automation to improve the accuracy and effectiveness of your security activities. You'll also learn how to design personalized security automation tools. While offensive security is a great way to stay ahead of emerging threats, defensive security plays an equal role in protecting organizations from cyberattacks. In this book, you'll get to grips with Python secure coding techniques to improve your ability to recognize dangers quickly and take appropriate action. As you progress, you'll be well on your way to handling the contemporary challenges in the field of cybersecurity using Python, as well as protecting your digital environment from growing attacks. By the end of this book, you'll have a solid understanding of sophisticated offensive security methods and be able to stay ahead in the constantly evolving cybersecurity space. What you will learn Familiarize yourself with advanced Python techniques tailored to security professionals' needs Understand how to exploit web vulnerabilities using Python Enhance cloud infrastructure security by utilizing Python to fortify infrastructure as code (IaC) practices Build automated security pipelines using Python and third-party tools Develop custom security automation tools to streamline your workflow Implement secure coding practices with Python to boost your applications Discover Python-based threat detection and incident response techniques Who this book is for This book is for a diverse audience interested in cybersecurity and offensive security. Whether you're an experienced Python developer looking to enhance offensive security skills, an ethical hacker, a penetration tester eager to learn advanced Python techniques, or a cybersecurity enthusiast exploring Python's potential in vulnerability analysis, you'll find valuable insights. If you have a solid foundation in Python programming language and are eager to understand cybersecurity intricacies, this book will help you get started on the right foot.
Data in extended ASCII character set.
Mode of access: Internet.